1995
DOI: 10.1248/bpb.18.396
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Glycation of Transferrin: Decrease of Iron-Binding Capacity and Increase of Oxygen Radical Production.

Abstract: The total iron-binding capacity (TIBC) and iron contents of diabetic rat serum, as well as the iron-binding capacity of glycated transferrin and oxygen radical production by the glycated proteins were examined. The TIBC and iron content of diabetic rat sera were found to be much lower than those of control rat sera. Incubation of human serum with glucose in vitro resulted in a significant fall of its unsaturated iron-binding capacity (UIBC) with time. When apotransferrin was incubated with glucose, its UIBC si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 1 publication
0
23
2
Order By: Relevance
“…Our study differs from previously reported studies 13,[26][27][28][29][30][31] in certain aspects. .irst, the offspring group from parents with DM2 was carefully matched to healthy individuals as far as medical history, age, sex, BMI and WHR are concerned.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study differs from previously reported studies 13,[26][27][28][29][30][31] in certain aspects. .irst, the offspring group from parents with DM2 was carefully matched to healthy individuals as far as medical history, age, sex, BMI and WHR are concerned.…”
Section: Discussioncontrasting
confidence: 99%
“…Since free metals are essential for the prooxidative effect, the question arises whether there are sufficient amounts of unbound metals in diabetic individuals to induce autooxidation of ascorbic acid. Glycation of proteins occurs in diabetes, and the binding capacity of transferrin to iron is reduced when this transport protein is glycated [68]. On the other hand, the relevance of glycation in vivo has been questioned [69].…”
Section: Discussionmentioning
confidence: 99%
“…The current study also shows a similar increase of glycation of transferrin during poor glycemic control. An in vitro study (40) demonstrated that nonenzymatic glycation of transferrin decreases the iron binding capacity by binding the iron ions loosely on the protein and also increasing the production of free oxygen radicals including O 2 Ϫ and OH. The current study indicates potential pathological changes that occur in diabetes.…”
Section: ) Paired Analysis Showed a Significant Difference In Glycamentioning
confidence: 99%